Primary caregivers, healthcare workers, teachers and community leaders' perceptions and experiences of their involvement, practice and challenges of disclosure of HIV status to children living with HIV in Malawi: A qualitative study - Kalembo, F.; Kendall, Garth; Ali, Mohammed; Chimwaza, A.; Tallon, Mary (BioMed Central Ltd, 2018)
Background: The World Health Organisation has recommended that healthcare workers, teachers and community leaders work with parents to support children living with HIV. The aim of this study was to assess the perceptions and experiences of primary caregivers and other care providers such as healthcare workers, teachers, and community leaders regarding their involvement, practice and challenges of HIV disclosure to children aged between 6 and 12 years living with HIV in Malawi. Methods: Twelve focus group discussions and 19 one-on-one interviews involving a total of 106 participants were conducted in all three administrative regions of Malawi. The interviews and focus group discussions explored perceptions and experiences regarding involvement, practice and challenges of disclosure of HIV status to children. Data were analysed using thematic analysis. Results: Primary caregivers, healthcare workers, teachers, and community leaders all reported that the disclosure of HIV status to children was not well coordinated because each of the groups of participants was working in isolation instead of working as a team. A "working together" model emerged from the data analysis where participants expressed the need for them to work as a team in order to promote safe and effective HIV status disclosure through talking about HIV, sharing responsibility and open communication. Participants reported that by working together, the team members would ensure that the prevalence of HIV disclosure to young children increases and that there would be a reduction in any negative impact of disclosure. Conclusion: Global resources are required to better support children living with HIV and their families. Healthcare workers and teachers would benefit greatly from training in working together with families living with HIV and, specifically, training in the disclosure process. Resources, in the form of books and other educational materials, would help them explain HIV and its effective management to children and families.